Retrospective survey of Dickeya fangzhongdai using a novel validated real-time PCR assay - Alič, Špela; Bačnik, Katarina; Dreo, Tanja (Frontiers in Microbiology, 2024)
Dickeya fangzhongdai, an aggressive plant pathogen, causes symptoms on a variety of crops and ornamental plants including bleeding canker of Asian pear trees. Historical findings stress the need for a specific detection tool for D. fangzhongdai to prevent overlooking the pathogen or assigning it to general Dickeya spp. Therefore, a qualitative real-time PCR for specific detection of D. fangzhongdai has been developed and validated. The developed assay shows selectivity of 100%, diagnostic sensitivity of 76% and limit of detection with 95% confidence interval in plant matrices ranging from 311 to 2275 cells/mL of plant extracts. The assay was successfully used in a retrospective survey of selected host plants of relevance to Europe and environmental niches relevant to D. fangzhongdai. Samples of potato tubers and plants, plants from the Malinae subtribe (apple, pear, quince, and Asian pear tree) and fresh surface water from Slovenia were analyzed. D. fangzhongdai was not detected in any plant samples, however, 12% of surface water samples were found to be positive.